OBSERVING THE REALITY OF PUBLIC SECTOR AUDIT IN ERADICATION OF CORRUPTION - Alkam, Rahayu; Saffanah, Nurina; Bangsawan, Achdian Anggreny (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2023)
This study aims to examine the reality of public sector audits in efforts to eradicate corruption in Indonesia. The analysis covers a number of aspects related to the implementation of public sector audits in supporting the eradication of corruption. The data was obtained using the perspective of seven experienced BPK auditors. In-depth interviews were conducted using semi-structured questions. The research results reveal a number of realities regarding public sector audits, namely the nature of public sector audits which are not specifically designed to routinely detect corruption, differences in the authority of examiners and law enforcers, and the relationship between auditors and auditees in the audit process. Therefore, to be more proactive in increasing the effectiveness of the public sector audit function in order to support the eradication of corruption, extensive efforts are needed both by individual auditors and by the BPK institutionally